Calypso - Sedaris, David (New York, NY : Little, Brown and Company, 2018)
Personal essays share the author's adventures after buying a vacation house on the Carolina coast and his reflections on middle age and mortality.
Company man -- Now we are five -- Little guy -- Stepping out -- A house divided -- The perfect fit -- Leviathan -- Your English is so good -- Calypso -- A modest proposal -- The silent treatment -- Untamed -- The one(s) who got away -- Sorry -- Boo-hooey -- A number of the reasons I've been depressed lately -- Why aren't you laughing? -- I'm still standing -- The spirit world -- And while you're up there, check on my prostate -- The Comey memo.
"May 2018"--Title page verso.
Keywords: Sedaris, David -- Anecdotes; Aging -- Anecdotes; Mortality; American wit and humor; Essays; Humor